Phytochemical Profile and Evaluation of the Antioxidant, Cyto-Genotoxic, and Antigenotoxic Potential of Salvia verticillata Hydromethanolic Extract - Lamprini S. Stavropoulou; Ioanna Efthimiou; Lambrini Giova; Chrysoula Manoli; Paraskevi S. Sinou; Aris Zografidis; Fotini N. Lamari; Dimitris Vlastos; Stefanos Dailianis; Maria Antonopoulou (Plants, 2024)
This study comprises the phytochemical characterization, the evaluation of the total phenolic content (TPC) and antioxidant activity (AA), and the investigation of the cyto-genotoxic and antigenotoxic potential of hydromethanolic extract derived from Salvia verticillata L. leaves. HPLC–DAD–ESI-MS and HPLC–DAD were used for the characterization of the extract and determination of the major ingredients. Afterwards, the TPC and AA were determined. The cytotoxic and genotoxic effect of the extract on cultured human lymphocytes at concentrations of 10, 25, and 50 μg mL−1 was investigated via the Cytokinesis Block MicroNucleus (CBMN) assay. Moreover, its antigenotoxic potential against the mutagenic agent mitomycin C (MMC) was assessed using the same assay. The hydromethanolic extract comprises numerous metabolites, with rosmarinic acid being the major compound. It had a high value of TPC and exerted significant AA as shown by the results of the Ferric Reducing Antioxidant Power (FRAP) and Radical Scavenging Activity by DPPH• assays. A dose-dependent cytotoxic potential was recorded, with the highest dose (50 μg mL−1) exhibiting statistically significant cytotoxicity. None of the tested concentrations induced significant micronuclei (MN) frequencies, indicating a lack of genotoxicity. All tested concentrations reduced the MMC-mediated genotoxic effects, with the two lowest showing statistically significant antigenotoxic potential.